2021
DOI: 10.1111/ijcp.14033
|View full text |Cite
|
Sign up to set email alerts
|

Nutrients that modulate gestational diabetes mellitus: A systematic review of cohort studies Jan 2019‐Jan 2020

Abstract: According to the American Diabetes Association, GDM is defined as the intolerance to glucose diagnosed during pregnancy, after the first trimester. 1 Both, insulin administration and diet control may be used for its treatment, although the symptoms may not resolve after pregnancy. Based on the available statistics, GDM occurs in up to 7% of pregnancies, which would mean 200 000 cases annually in the United States. 2 GDM screening should be undertaken during the first prenatal visit and, if this is not positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Some studies have suggested that folic acid supplementation is associated with the development of GDM [ 17 , 18 , 19 , 20 , 21 ], but the conclusions are equivocal. A previous study [ 19 ] included 14,553 women in the Nurses’ Health Study II cohort and showed that folic acid supplementation before pregnancy was negatively correlated with the risk of GDM.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have suggested that folic acid supplementation is associated with the development of GDM [ 17 , 18 , 19 , 20 , 21 ], but the conclusions are equivocal. A previous study [ 19 ] included 14,553 women in the Nurses’ Health Study II cohort and showed that folic acid supplementation before pregnancy was negatively correlated with the risk of GDM.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that the central link in the pathogenesis of GDM is the imbalance between insulin resistance and pancreatic β‐cell secretion defects 5 . In recent years, accumulating evidence has also demonstrated that genetics, environment, inflammatory factors, adipocytokines, ferritin overload, oxidative stress and other comprehensive factors also play important roles in the incidence of GDM 6,7 . Therefore, in‐depth research on the etiology of GDM is of great significance for early pregnancy screening, prenatal care guidance, reducing the incidence of GDM, and improving maternal and child outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…5 In recent years, accumulating evidence has also demonstrated that genetics, environment, inflammatory factors, adipocytokines, ferritin overload, oxidative stress and other comprehensive factors also play important roles in the incidence of GDM. 6,7 Therefore, in-depth research on the etiology of GDM is of great significance for early pregnancy screening, prenatal care guidance, reducing the incidence of GDM, and improving maternal and child outcomes.Oxidative stress plays a crucial role in the occurrence of GDM. 8 Oxidative stress during pregnancy leads to the production of large amounts of reactive oxygen species (ROS).…”
mentioning
confidence: 99%